Shifting Malaysian primary science teachers' assessment literacy for a world class education - Sathasivam, R.V.; Daniel, E.G.S. (2011)
One of the challenges for science teachers in the 21st Century is to ensure high standards in the process of student assessment. Assessment literacy is important because teachers spend up to 50% (Plake, 1993) of time in their profession assessing students. Assessment literacy does not only cover the technical aspects of testing but has moved on to encompass almost all interactions that teachers have with their students, school authorities and parents. This paper will describe part of bigger study conducted to ascertain the assessment literacy of selected Malaysian primary science teachers. Using qualitative data collection techniques such as teacher journals and interviews with jive primary school science teachers, the findings showed that teachers' knowledge on assessment literacy stemmed more from the behaviourist perspective and that external examinations still dominated what drives teachers' ideas about their practices. It was also found that in-depth knowledge on how to conduct formative assessment practices were limited. The study indicated clear implications on how teachers would conduct their assessment practices in their classrooms and how their knowledge on assessment would affect their students' understanding of scientific concepts. Based on these findings, how primary science teachers' assessment literacy can be shifted to a world class level is put forward.